Urinary biopyrrins: A new marker of oxidative stress in psoriasis - Ola Ahmed Bakry; Sally El Hefnawy; Alaa Hassan Mariee; Yara El Gendy (Wolters Kluwer Medknow Publications, 2016)
Background: Psoriasis is a common chronic, relapsing, immune-mediated disease involving skin and joints of genetically predisposed individuals. Oxidative stress has been found to play many important roles in cellular damage and loss of function in a number of tissues and organs and is believed to contribute to the pathogenesis of a variety of diseases. Urinary biopyrrin levels have gained attention as an indicator of oxidative stress. Aim and Objective: To measure urinary biopyrrins excretion as a marker of oxidative stress in psoriasis. Patients and Methods: This case-control study was carried out on 85 subjects; 55 cases with chronic plaque psoriasis and 30 age, gender and body mass index-matched normal subjects as a control group. Urinary biopyrrin levels were measured using enzyme immunoassay. Results: There was a highly significant difference between cases and controls regarding urinary biopyrrins level (P < 0.001). There was significant positive correlation between biopyrrins level and both the age of cases (r = 0.28, P = 0.01) and psoriasis area and severity index score (r = 0.99, P < 0.001). Conclusion: Urinary biopyrrins are increased in patients with psoriasis, and the level is correlated with disease severity. Further large-scale studies involving different ages and different clinical varieties of the disease are needed to expand and validate current findings. The clinical usefulness of antioxidants in psoriasis treatment needs to be evaluated in future research. Furthermore, the value of biopyrrins as biomarkers for monitoring response to therapy needs to be evaluated.